(untitled) (Scientia Agricola, 2013)
Feed shortages are relatively frequent in subtropical pasture-based dairy production systems. The effect of feed restriction on milk yield and physical-chemical traits was evaluated in this study. The experiment was carried out in Brazil's south region. Treatments consisted of control and restricted diet. Six multiparous and six primiparous cows, with 499 ± 47.20 kg body weight (BW), at mid-lactation (188 ± 124 days in milk), producing 19.35 ± 4.10 kg of milk were assigned to two groups, balanced for parity, each group receiving a different sequence of the dietary treatments for 56 days, in a crossover design. Diet nominated as control included 8 kg DM 100 kg BW-1 of Bermuda grass var. Tifton pasture (Cynodon dactylon (L.) Pers.), 5.00 kg of concentrate and 2.50 kg of Tifton hay per day. The restriction diet consisted of 50 % of the quantity offered in the control diet. Milk production and physicochemical composition were evaluated. Feed restriction reduced milk production by 40 %, body condition score by 5 %, milk magnesium by 14.3 %, lactose by 1.7 %, titratable acidity by 10 % and stability to the ethanol test by 9 % and it tended to increase (7 %) milk potassium content. No changes were found for the remaining characteristics. Since feed restriction is quite frequent in Brazil's extensive dairy production systems, our concern is that besides decreased milk production, changes can occur in the physiochemical attributes of the milk, mainly a reduction in the stability to the ethanol test, which may increase the volume of milk rejected by the industry.